PENINGKATAN MOTIVASI BELAJAR DAN KERJASAMA DALAM KELOMPOK MENGGUNAKAN MEDIA WORDWALL - Lamanepa, Agustina S.P; Nai, Firmina Angela; Pono, Chatrina (Jurnal Lazuardi, 2024)
The focus of this research is "Increasing learning motivation and collaboration in groups using wordwall media". The aim of this research is to find out and describe how to increase learning motivation and collaboration in groups using wordwall media. This research was carried out in class XI-7 of SMA Negeri 2 Kupang for 3 cycles. In initial observations, researchers used text media in the form of Student Worksheets which were carried out by students with group members of 5-6 people, but during the discussion the students were less active in the group. Based on this problem, researchers applied wordwall media in learning. Wordwall is an interactive learning media that teachers can use. In Cycle 1, researchers used a random wheel wordwall, students were formed into groups with 4 members. Together with their group they will spin the random wheel until the wheel stops and a question will appear which will be answered directly. Then in cycle 2 the wordwall used was to open the box, where students and their groups took the quiz provided with 10 numbers and the results were visible, students had started to be active and had even started to collaborate with each other in determining the correct answer. Then in cycle 3, namely the word wall searching for words, the students were very active and even divided the task to each group member to find the word they were looking for. The use of wordwall media in this learning produces good and satisfying learning results. This can be seen directly as a reflection of the learning experience and can be proven by the presentation results of students who completed the percentage at 75%, and the percentage of students who did not complete it at 25%.